2011
DOI: 10.1021/cm2021593
|View full text |Cite
|
Sign up to set email alerts
|

Direct Attachment of Oligonucleotides to Quantum Dot Interfaces

Abstract: A straightforward functionalization strategy for the direct attachment of single-stranded oligonucleotides (ssDNA) to quantum dot (qdot) interfaces is described. The approach takes advantage of a histidine-mediated phase transfer protocol that results in qdots with high colloidal stability in aqueous buffers. The weakly bound histidine encapsulation facilitates monolayer exchanged with both thiolated ssDNA and polyhistidine-tagged proteins. The successful biomodification at the qdot interface was probed by FRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 103 publications
0
24
0
Order By: Relevance
“…The Maye group developed a grafting process for the attachment of oligonucleotide strands to CdSe/ZnS core-shell quantum dots (Han et al, 2011) using the procedure illustrated in Fig. 3.…”
Section: Fluorophores Quenchers and Modifications In Mbsmentioning
confidence: 99%
“…The Maye group developed a grafting process for the attachment of oligonucleotide strands to CdSe/ZnS core-shell quantum dots (Han et al, 2011) using the procedure illustrated in Fig. 3.…”
Section: Fluorophores Quenchers and Modifications In Mbsmentioning
confidence: 99%
“…The CdSe QD cores with ZB crystal structure were synthesized by standard methods. [35][36][37][38][39] In a typical synthesis, 0.103 g (0.802 mmol) of CdO in 12 mL oleic acid (OAc) and 5.0 mL ODE was heated to 230 C forming a colourless solution of Cd-oleate. Next, 0.021 mol of dodecylamine (DDA) and 2.002 g trioctylphosphine oxide (TOPO) was introduced and the mixture heated to 270 C until a colourless solution was obtained.…”
Section: Synthesismentioning
confidence: 99%
“…The oligonucleotides were then hybridized with Cy3labeled complements to generate FRET. At the opposite extreme, Han et al developed a method for directly functionalizing QD550 with a dense layer of oligonucleotide ligands ($40 per QD) or, alternatively, SA-His 6 for modification with biotinylated oligonucleotides [260]. Minimal changes in FRET efficiency were observed, indicating that the oligonucleotides had a tendency to adsorb to the surface of the QD.…”
Section: Conformational Insights From Qd-fretmentioning
confidence: 99%
“…The effect of the surface of the QD on oligonucleotide conformation was investigated by measuring the FRETefficiency for oligonucleotide probes with two different linker lengths, and by switching the Cy3 label between the proximal and distal terminus of the complement. This result was attributed to a lower density of oligonucleotides, permitting an average conformation that more closely approached the QD [260]. Additional experiments and FRET studies suggested that the adsorptive interactions were driven by hydrogen bonding between the neutral MPA ligands and nucleobases; the extent of adsorption was affected by changes in pH, ionic strength, base sequence, and the presence of chaotropic agents [231,259].…”
Section: Conformational Insights From Qd-fretmentioning
confidence: 99%